(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
In contemporary times, learning spaces have been undergoing changes, as well as the agents participating in this process. One of the environments that emerge as a learning territory are digital social networks, in the case of this study, Instagram. In this context, as sharing agents of a theme that can be taught and learned, there are digital fashion influencers. We seek to identify the characteristics and components of these professionals that allow the teaching of transmitted content. For this, we use the concept of educator constituted in a Freirean tradition. Through the realization of a rich and diverse methodology, structured from the netnographic method, we identified nine components that make the teaching and learning process possible. These components were grouped into three characteristics: individual, relational, and contextual and language.